2018
DOI: 10.1080/23279095.2018.1490288
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric Complex Figure Test: A test for the assessment of planning, visual spatial ability, and memory in older adults

Abstract: The present study describes the development of a simplified complex figure for older adults. This new figure is based on theoretical organizational strategy models developed for the Rey Complex Figure Test and combines several new technologies for the enhancement of the data capture. The study shows that the accuracy and memory scores for the new measure correlate significantly with Trail Making Test, Five Point Test, and RBANS Complex Figure scores. The new figure's strategy scores correlate with predominantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Some studies have developed multiple simplified versions of the ROCF to solve the above-mentioned problems. Poreh et al ( 22 ) developed a simplified ROCF ( Figure 1K ) and found that its copying, recall, and strategy scores are well-distributed among healthy older people (over 60 years old), indicating that it is more suitable for the elderly than the classical ROCF. Similarly, de Paula et al ( 23 ) developed a simplified Taylor figure ( Figure 1J ) and verified the validity and the reliability of its assessment of the visuospatial ability of the low-educated elderly (primary school).…”
Section: Versions Of Complex Figure Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have developed multiple simplified versions of the ROCF to solve the above-mentioned problems. Poreh et al ( 22 ) developed a simplified ROCF ( Figure 1K ) and found that its copying, recall, and strategy scores are well-distributed among healthy older people (over 60 years old), indicating that it is more suitable for the elderly than the classical ROCF. Similarly, de Paula et al ( 23 ) developed a simplified Taylor figure ( Figure 1J ) and verified the validity and the reliability of its assessment of the visuospatial ability of the low-educated elderly (primary school).…”
Section: Versions Of Complex Figure Testmentioning
confidence: 99%
“…Subsequently, Poreh et al ( 22 ) used a new technology (digital pen) to capture the drawing process and recorded the movement of the pen to the laptop through an infrared receiver. It realized the semi-automatic analysis of Bennett-Levy scoring and found that the symmetry score can be a good marker for non-verbal executive function.…”
Section: Digital Complex Figure Testmentioning
confidence: 99%
“…It is an organizational strategy model based on the classic ROCF test. Its copying, recall, and strategy scores are well-distributed among healthy older people (over 60 years old), indicating that it is more suitable for the elderly than the ROCF 19 . Using the simplified figure can avoid the overlap of strokes, which is conducive to recognizing each stroke with digital equipment in a limited space.…”
Section: Introductionmentioning
confidence: 99%
“…However, neither of these studies evaluated the drawing order but focused on identifying outlines and details related to traditional scoring methods. Previously, only two studies used digital devices (such as a digital pen 19 or tablet 20 , 21 ) to capture the drawing process and analyzed the subjects' drawing behavior patterns by extracting spatial, procedural, and kinematic dimension parameters. Poreh et al 19 used a digital pen to capture the drawing process and recorded the movement of the pen to the laptop through an infrared receiver.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation